Functional domain analysis of SOX18 transcription factor using a single-chain variable fragment-based approach. Issue 4 (19th May 2018) - Fontaine, Frank R.; Goodall, Stephen; Prokop, Jeremy W.; Howard, Christopher B.; Moustaqil, Mehdi; Kumble, Sumukh; Rasicci, Daniel T.; Osborne, Geoffrey W.; Gambin, Yann; Sierecki, Emma; Jones, Martina L.; Zuegg, Johannes; et al.
ABSTRACT: Antibodies are routinely used to study the activity of transcription factors, using various in vitro and in vivo approaches such as electrophoretic mobility shift assay, enzyme-linked immunosorbent assay, genome-wide method analysis coupled with next generation sequencing, or mass spectrometry. More recently, a new application for antibodies has emerged as crystallisation scaffolds for difficult to crystallise proteins, such as transcription factors. Only in a few rare cases, antibodies have been used to modulate the activity of transcription factors, and there is a real gap in our knowledge on how to efficiently design antibodies to interfere with transcription. The molecular function of transcription factors is underpinned by complex networks of protein-protein interaction and in theory, setting aside intra-cellular delivery challenges, developing antibody-based approaches to modulate transcription factor activity appears a viable option. Here, we demonstrate that antibodies or an antibody single-chain variable region fragments are powerful molecular tools to unravel complex protein-DNA and protein-protein binding mechanisms. In this study, we focus on the molecular mode of action of the transcription factor SOX18, a key modulator of endothelial cell fate during development, as well as an attractive target in certain pathophysiological conditions such as solid cancer metastasis. The engineered antibody we designed inhibits SOX18 transcriptional activity, by interfering specifically with an 8-amino-acid motif in the C-terminal region directly adjacent to α-Helix 3 of SOX18 HMG domain, thereby disrupting protein-protein interaction. This new approach establishes a framework to guide the study of transcription factors interactomes using antibodies as molecular handles.